Effects of WeChat use on the subjective health of older adults - Wei, Ning; Sun, Dingqiang; Huang, Wenhao (Frontiers in Psychology, 2022)
Objectives: In this study, the effect of WeChat use on the subjective health of elderly people is examined using elderly people in China as subjects. Methods: We innovatively used mobile phone use by elderly people as an instrumental variable to eliminate the possible endogeneity problem of ordinary least squares (OLS) estimation. Results: Analyses of the 2018 China Health and Retirement Longitudinal Study (CHARLS) survey data indicate that WeChat use has a significant positive impact on the subjective health of elderly people and can significantly improve their self-rated health and mental health status. WeChat use has significant positive effects on the subjective health of both elderly men and women, but younger elderly people obtain more health benefits from WeChat use. Conclusion: The virtual social participation prompted through WeChat use affects the health of elderly people, a finding that provides a reference for the promotion of the active integration of elderly people into digital life.